The effect of carbohydrate-protein and carbohydrate beverages on subsequent exercise capacity and hormonal markers of recovery - Coyle, Colin J. (Trinity College (Dublin, Ireland). Department of Physiology, 2012)
Recovery requires the restoration of physiological and psychological mechanisms and is heavily influenced by the availability and actions of specific hormones and nutrients (Mujika et al., 1996; Kraemer et al., 1998; Filaire et al., 2001). Cortisol (C) and testosterone (T) influence the regeneration phase post-exercise through modulation of anabolic and catabolic processes, and are reported to respond to even slight increases in training load (Coutts et al., 2007). The ingestion of a combined carbohydrate and protein supplement (CHO-PRO) immediately post-exercise has been reported to mediate greater muscle glycogen resynthesis compared with CHO alone (Ivy et al, 2002) as well as significantly improving time to failure in subsequent exercise (Betts et al., 2007). Data suggested that nutritional interventions may suppress the exercise-induced increase in C by providing sufficient exogenous CHO to maintain blood glucose (BGlu) concentration so that muscle glycogen is spared during subsequent exercise, or restored post-exercise (Henson et al., 1998; Bishop et al., 1999b; Gleeson & Bishop, 2000; Bangsbo et al., 2006; Krustrup et al., 2006a; Lane et al., 2010).
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin